Council unbound the growth of UN decision making on conflict and postconflict issues after the Cold War - Matheson, Michael John (United States Institute of Peace Press, 2006)
"In this book, Michael Matheson examines the Security Council's new, expansive exercise of legal authority in this period and its devising of bold and innovative methods - coercive and noncoercive - to stop nascent wars and "threats to the peace," including international terrorism. He also surveys the many roles assumed by the Council in postconflict environments, acting in a variety of ways to rebuild a war-torn country or territory and reintegrate it into the world community - from prosecuting war criminals, to providing compensation for war victims, to exercising governmental authority in postconflict territories such as Cambodia, Bosnia, and recently, Kosovo and East Timor. The author also examines the more recent controversies over Iraq, in which disagreements among the permanent members have made decisive UN action difficult, and the investigations into fraud and abuse in various UN programs."--BOOK JACKET